2019
DOI: 10.1038/s41598-018-36932-w
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome and transcriptome-wide effects of the carbon storage regulator A in enteropathogenic Escherichia coli

Abstract: The carbon storage regulator A (CsrA) is a conserved global regulatory system known to control central carbon pathways, biofilm formation, motility, and pathogenicity. The aim of this study was to characterize changes in major metabolic pathways induced by CsrA in human enteropathogenic Escherichia coli (EPEC) grown under virulence factor-inducing conditions. For this purpose, the metabolomes and transcriptomes of EPEC and an isogenic ∆csrA mutant derivative were analyzed by untargeted mass spectrometry and RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 90 publications
5
57
0
Order By: Relevance
“…A study conducted in EPEC showed that deletion of csrA resulted in a significant change in over half of the metabolites observed (Berndt et al, 2019). In line with previous work conducted in CsrA transposon insertion mutants, the deletion led to an accumulation of glycogen and fructose-6-phosphate (Berndt et al, 2019).…”
Section: New Connections From Systems-based Approachessupporting
confidence: 72%
See 1 more Smart Citation
“…A study conducted in EPEC showed that deletion of csrA resulted in a significant change in over half of the metabolites observed (Berndt et al, 2019). In line with previous work conducted in CsrA transposon insertion mutants, the deletion led to an accumulation of glycogen and fructose-6-phosphate (Berndt et al, 2019).…”
Section: New Connections From Systems-based Approachessupporting
confidence: 72%
“…Studies in E. coli Nissle 1917 revealed that the influence of CsrA on metabolite levels and metabolic flux were conditional, differing dependent upon the metabolic fate of the carbon source that was used for growth (Revelles et al, 2013). A study conducted in EPEC showed that deletion of csrA resulted in a significant change in over half of the metabolites observed (Berndt et al, 2019). In line with previous work conducted in CsrA transposon insertion mutants, the deletion led to an accumulation of glycogen and fructose-6-phosphate (Berndt et al, 2019).…”
Section: New Connections From Systems-based Approachessupporting
confidence: 60%
“…−1.25 at late-log phase) which is involved in making exopolysaccharide colanic acid (M-antigen) which increases E. coli's ability to survive in environmental stresses 52 . Recently, this ability was shown to be regulated through the master regulator csrA 53 , which was up-regulated at unrestricted DO in this study. A schematic representing the state of the major metabolic processes and regulators in E. coli at restricted and unrestricted DO during rARU expression are presented in Fig.…”
Section: Transcriptomic and Proteomic Response To Restricted And Unresupporting
confidence: 52%
“…The organic phase was discarded, and 1 mL of the aqueous phase was evaporated to dryness. Sample preparation, GC–MS analysis, data pre-processing and metabolite identification were performed as described by Berndt et al [ 12 ]: Metabolite extracts were derivatised by methoxyamine/pyridine and silylated using MSTFA to volatilise the analytes. The samples were separated on a 30 m column with a stationary phase of 5% phenyl arylen and 95% dimethylpolysiloxane material (ZB-5MS ® , Phenomenex, Torrance, CA, USA) using a temperature gradient from 70 C to 330 C over 32.5 min.…”
Section: Methodsmentioning
confidence: 99%